Bibionidae (Diptera) from mid-Cretaceous Myanmar amber: the genera Protopenthetria Li et al., 2021 and Penthetria Meigen, 1803 - Skartveit, John; Nel, André; Kundura, Jean-Paul; Ševčík, Jan (Zootaxa, 2025)
We describe the earliest known representatives of the subfamily Hesperininae, and species of the extant genus Penthetria, from mid-Cretaceous amber of Myanmar. Penthetria is represented by Penthetria tenue sp. nov. and Penthetria tipuloides sp. nov. We also describe seven new species in the recently described genus Protopenthetria Li et al, 2021, which we also provisionally place in Hesperininae. In the nominate subgenus we describe Protopenthetria (s.str.) rectangula sp. nov. and P. (s.str.) longicornis sp. nov. which are probably related to Protopenthetria skartveiti Li et al., 2021. The new subgenus Megacephaletria subgen.n. is described, including five species, Protopenthetria (Megacephaletria) bicoloripes sp. nov., P. (M.) coronata sp. nov., P. (M.) crassitarsalis sp. nov., P. (M.) globistylus sp. nov. and P. (M.) pallipes sp. nov. The present results suggest that Myanmar amber includes a species-rich fauna of bibionid flies.